Liminalitas Perempuan Arab, Migrasi, dan Kota dalam Novel Innahâ London, Yâ Azîzî Karya Hannan Asy-Syaikh - Mahmudah, Mahmudah (Arabi : Journal of Arabic Studies, 2023)
This paper aims to explore the relationship between Arab women, migration, and the city in Hannan asy-Syaikh’s Innaha London, ya Azizi. The meeting of two cultures can be seen as a liminality and involves a postcolonial feminist discourse, considering that the women come from a former colonized country and the host country is a former colonizer country. Liminality describes the ‘between space’ as a place where cultural change occurs. The method used is the dialectical method. Research shows that liminality is related to language, food, and the relationship between women and men. Liminality becomes a bridge in bringing together self-culture with urban culture. It shows that at first, they didn’t understand and admire each other, but finally realized that they didn’t have to change to become the other. Each can remain self without losing identity and dominating the other. Liminality restores and strengthens the Arab identity of Arab migrant women in European metropolitan cities.